Collision Tumors of the Colon and Peritoneum: Signet-Ring Cell Carcinoma and Granular Cell Tumor - Dorela-Codruta Lazureanu; Denisa Anderco; Sorin Dema; Aura Jurescu; Remus Cornea; Octavia Vita; Bogdan Tunescu; Sorina Taban (Life, 2023)
Collision tumors, although rare, characterized by two distinctive (morphological, as well immunohistochemical) and spatially independent tumor components at the same location, are always puzzling for clinicians, pathologists, and patients because they do not fit into the usual approaches, being neither diagnostic nor therapeutic. Reviewing the specialized literature, to date, collision tumors have been reported in multiple locations such as the skin, esophagus, stomach, intestine, liver, kidney, bladder, adrenal gland, or thyroid. We report a case of coexistence at the same site of a malignant tumor of the ascending colon and a benign tumor emerging from the peritoneal lining, initially thought by the surgeon to be right-sided serosal carcinomatosis. But histopathological examination reveals that those multiple serosal nodules were benign granular cell tumors that have collided with highly aggressive transparietal signet-ring colon carcinoma. These results put the patient’s prognosis and therapeutic strategy in a different light than the clinical and intraoperative evaluation.